PARTICULARITICS OF THE INFORMING AND OF THE INFORMED CONSENT IN PEDIATRICS - Liliana Buta; Iulia Alexandru Buta (Amaltea Medical Publishing House, 2008)
The specificity of informing the sick child involves the care personnel, but also the parents or tutors who must exercise their responsibilities in taking decisions concerning the medical acts regarding the child. The material informing is beneficial for the sick child, because it answers the needs specific to all the children and especially to need of respecting the child as a human being and of considering him as a subject and not as an object of the medical cares. As concerns the minor, who does not have the capacity to give his/her consent, an intervention can be made only if his/her legal representative, or other authority or other person or instance designated by the law, gave his/her authorization. In Romania, the age for expressing the informed consent is 18 years when the minor, from a juridical point view, acquires the exercise capacity. The preschool child does not have the aptitudes to participate in taking decisions and consequently his/her legal representative must approve or refuse the medical intervention, representing the sick child's interest. The school age minor may participate in raking medical decisions, but he/she dose not have the full capacity of deciding, the consent being given by the legal representative, until the age of 14 years. The child having the age between 14-18 years, considered to have restricted exercise capacity, may give his/her consent only after having previously informed his/her parents. The teenager who is already 16 years old may express his consent in his/her parents' absence in case treatments regarding sexual or reproductive apparatus disease, at his/her express request, or in case of emergencies